2007
DOI: 10.1080/17458080701376348
|View full text |Cite
|
Sign up to set email alerts
|

CNT composites for aerospace applications

Abstract: Carbon nanotubes were synthesized by thermal arc plasma process after optimization of the synthesis parameters. These samples were then analysed by scanning and transmission electron microscopes (SEM and TEM), in order to establish the morphology of the nanostructures. Atomic force microscopy (AFM) and electron diffraction studies were also carried out before using the sample for the composite material preparation. Composites of epoxy resin with curing agent as well as a mixture of graphite and carbon nanotube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…The shielding efficiency was enhanced by combination of different fillers in the same polymer matrix. Bellucci, et al [9] studied the resistivity of composite materials with varying percentages of thermal arc plasma processed CNTs added to the epoxy resin. The electrical resistivity of the material was studied under varying humidity, temperature and voltage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The shielding efficiency was enhanced by combination of different fillers in the same polymer matrix. Bellucci, et al [9] studied the resistivity of composite materials with varying percentages of thermal arc plasma processed CNTs added to the epoxy resin. The electrical resistivity of the material was studied under varying humidity, temperature and voltage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…CNT exceptional electrical, mechanical, and thermal properties have been exploited in many studies to improve these properties in other materials. It has been observed that various polymers [10][11][12][13][14][15][16][17][18][19][20][21][22], ceramics [23,24], and epoxies [25][26][27][28][29][30][31][32] see enhancements in these properties when blended with CNTs to form composites. [32][33][34][35][36][37][38][39][40] The focus of this work is electronic transport in nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin combined with carbon nanotubes (CNTs), principally of the multi-wall (MW) type, is largely adopted for the production of advanced composites that can be used in the aerospace industry [3,4]. In fact, driven by the significant weight reduction, such materials may be a valid alternative to the classical metal for the realization of structural parts in new generation aircraft fuselage or cockpit, for which ability to dissipate lightning currents or provide effective shielding again electromagnetic interference is required.…”
Section: Introductionmentioning
confidence: 99%